Annual Plan of Bhutan 1972-73 Report of the Technical Team - Planning Commission (Planning Commission, 1972)
The Ministry of External Affairs requested the Planning Commission to depute a Technical Team to visit Bhutan for finalization of the Bhutan’s Annual Plan 1972-73. Accordingly, the Planning Commission constituted a Team consisting of the following officials.
Government of India Planning Commission
Government of India Planning Commission